2014
DOI: 10.4238/2014.december.18.7
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional identification of a novel BCA3 splice

Abstract: ABSTRACT. The human breast cancer-associated gene (BCA3) was first discovered in breast and prostate cancer cells lines. In vivo studies have shown that BCA3 is mainly expressed in breast tumor cells and not in normal breast and prostate tissues. To date, 3 splice variants of BCA3 have been reported: a double-absent variant lacking exon 3 and exon 5 (BCA3-1), an exon 3-absent variant (BCA3-2), and full-length BCA3. In this study, we investigated whether a novel BCA3 splice variant exists that lacks only the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Nevertheless, neither highly nor lowly expressed AKIP1 enhanced NF-κB activity. This finding contrasts with previous works by Zhang et al (2014) or Gao et al Vol. 68 (2008), in which the same cell line (HEK-293) and the same dual reporter assay (DLR) were used and AKIP1 was expressed from a similar expression plasmid, pcDNA3.1-FLAG.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, neither highly nor lowly expressed AKIP1 enhanced NF-κB activity. This finding contrasts with previous works by Zhang et al (2014) or Gao et al Vol. 68 (2008), in which the same cell line (HEK-293) and the same dual reporter assay (DLR) were used and AKIP1 was expressed from a similar expression plasmid, pcDNA3.1-FLAG.…”
Section: Discussioncontrasting
confidence: 99%
“…AKIP1, PKAc, inhibitor of NF-κB (IκB) and p65 subunit of NF-κB form an inactive cytosolic complex that may be Vol. 68 modulated through PKA activators (Zhang et al 2014). Phosphorylation of p65 subunit by PKA is essential for the activation and translocation of NF-κB p65/p50 into the nucleus where it regulates transcription of target genes (Hayden andGhosh 2008, Gilmore 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has investigated the effects of AKIP1 in breast cancer cells [ 16 ], but to date, this has not been investigated in myometrium. As labour is believed to be an inflammatory process, AKIP1 may function as a molecular switch in myometrium, promoting NFκB activitation; It has been reported that in breast cancer tissue there are at least three different splice variants of AKIP1 [ 26 ], further more these have distinct cellular localization [ 27 ] and different affinity binding for PKAc [ 28 ] and such could have an impact of NFκB activation. It would be beneficial, to investigate in more detail if and how the splicing of AKIP1 changes during in parturition.…”
Section: Discussionmentioning
confidence: 99%